A piggy bank for healthcare: Why the health system needs old-age reserve funds - Kristian Niemietz (Institute of Economic Affairs (IEA), 2017)
Healthcare spending as a proportion of GDP has almost doubled since 1990, from just over 5% to almost 10% now. Healthcare costs rise exponentially in old age. Healthcare costs per capita are relatively stable during the first five decades of life, but they quadruple over the next four decades. This means that most healthcare spending represents a transfer from the working-age generation to the retired generation. The combination of rising life expectancy and low birth rates is a demographic pincer movement for the health system. The ratio of people of retirement age to people of working age currently stands at 28 to 100. This is forecast to rise to 47 to 100 by 2064. The Office for Budget Responsibility (OBR) predicts only modest increases in NHS spending as a proportion of GDP, but this forecast is predicated on the heroic assumption that the NHS is going to double its long-term productivity growth rate. The basic problem is that the NHS is financed on a pay-as-you-go basis. The alternative would be a prefunded system that builds up old-age reserves (comparable to pension funds) for people of working age, and then draws upon them when people retire. In such a system, population ageing would be much less of a problem, because as the number of elderly people grows, the reserves accumulated in the old-age funds would grow alongside. The NHS could begin to build up a similar old-age reserve fund. This would require a one-off increase in taxes, or spending cuts in the non-healthcare budget. But it would prevent steeper tax increases (or spending cuts) in the future. While the basic idea of prefunding is simple, a lot of details would need to be worked out first, the idea of prefunding healthcare expenditure is not even part of our current healthcare debate. It should be.
Keywords: I18; I13; H51; H83; I18; I13; H51; H83; 330